Sarcopenic obesity and cognitive performance - Tolea MI; Chrisphonte S; Galvin JE (Clinical Interventions in Aging, 2018)
Magdalena I Tolea,1 Stephanie Chrisphonte,1 James E Galvin1,2 1Charles E. Schmidt College of Medicine, Department of Integrated Medical Sciences, Comprehensive Center for Brain Health, Florida Atlantic University, Boca Raton, FL, USA; 2Christine E. Lynn College of Nursing, Louis and Anne Green Memory and Wellness Center, Florida Atlantic University, Boca Raton, FL, USA Background: Sarcopenia and obesity both negatively impact health including cognitive function. Their coexistence, however, can pose an even higher threat likely surpassing their individual effects. We assessed the relationship of sarcopenic obesity with performance on global- and subdomain-specific tests of cognition. Patients and methods: The study was a cross-sectional analysis of data from a series of community-based aging and memory studies. The sample consisted of a total of 353 participants with an average age of 69 years with a clinic visit and valid cognitive (eg, Montreal Cognitive Assessment, animal naming), functional (eg, grip strength, chair stands), and body composition (eg, muscle mass, body mass index, percent body fat) measurements. Results: Sarcopenic obesity was associated with the lowest performance on global cognition (Est.Definition1=−2.85±1.38, p=0.039), followed by sarcopenia (Est.Definition1=−1.88±0.79, p=0.017) and obesity (Est.Definition1=−1.10±0.81, p=0.175) adjusted for sociodemographic factors. The latter, however, did not differ significantly from the comparison group consisting of older adults with neither sarcopenia nor obesity. Subdomain-specific analyses revealed executive function (Est.Definition1=−1.22±0.46 for sarcopenic obesity; Est.Definition1=−0.76±0.26 for sarcopenia; Est.Definition1=−0.52±0.27 for obesity all at p0.05) and orientation (Est.Definition1=0.59±0.26 for sarcopenic obesity; Est.Definition1=−0.36±0.15 for sarcopenia; Est.Definition1=−0.29±0.15 all but obesity significant at p<0.05) as the individual cognitive skills likely to be impacted. Potential age-specific and depression effects are discussed. Conclusion: Sarcopenia alone and in combination with sarcopenic obesity can be used in clinical practice as indicators of probable cognitive impairment. At-risk older adults may benefit from programs addressing loss of cognitive function by maintaining/improving strength and preventing obesity. Keywords: sarcopenia, obesity, sarcopenic obesity, cognition, cross-sectional studies